DETERMINAN STRUKTUR MODAL PADA BANK PERKREDITAN RAKYAT DI TANGERANG TAHUN 2013 - 2017 - Khorida AR; Eko Narto Utomo (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The purpose of this study is to determine the effect of Liquidity and Tax on capital structure in the perspective of pecking order theory. The population in this study is the Bank Perkreditan Rakyat (BPR) company in Tangerang for the period 2013-2017. With the purposive sampling method obtained a total sample of 45 Bank Perkreditan Rakyat (BPR). Model analysis using multiple linear regression analysis. Using the F-test to determine the simultaneous influence between company characteristics and capital structure. Using the ttest to test the partial correlation of each independent variable on the capital structure. The results showed that the liquidity variable had a positive and significant effect on the capital structure. While the tax size variable has a positive and not significant effect on the capital structure.Keywords : DER (Debt to Equity Ratio), CR (Current Asset), Tax